The methane absorption spectrum near 1.73 µm (5695–5850 cm−1): Empirical line lists at 80 K and 296 K and rovibrational assignments. (July 2018) - Ghysels, M.; Mondelain, D.; Kassi, S.; Nikitin, A.V.; Rey, M.; Campargue, A.
Highlights: Spectra of methane recorded at 80 K and 297 K near 1.75 µm. The studied region corresponds to the highly congested central part of the Tetradecad. About 4000 and 2300 lines are measured at 297 and 80 K, respectively. The 2-Temperature method is applied to derive 1689 empirical lower state energies. Rovibrational assignments are provided for 2090 transitions. Abstract: The methane absorption spectrum is studied at 297 K and 80 K in the center of the Tetradecad between 5695 and 5850 cm −1 . The spectra are recorded by differential absorption spectroscopy (DAS) with a noise equivalent absorption of about α min   ≈ 1.5 × 10 −7 cm −1 . Two empirical line lists are constructed including about 4000 and 2300 lines at 297 K and 80 K, respectively. Lines due to 13 CH4 present in natural abundance were identified by comparison with a spectrum of pure 13 CH4 recorded in the same temperature conditions. About 1700 empirical values of the lower state energy level, Eemp, were derived from the ratios of the line intensities at 80 K and 296 K. They provide accurate temperature dependence for most of the absorption in the region (93% and 82% at 80 K and 296 K, respectively). The quality of the derived empirical values is illustrated by the clear propensity of the corresponding lower state rotational quantum number, Jemp, to be close to integer values. Using an effective Hamiltonian model derived from a previously published ab initio potential energy surface, about 2060 lines are rovibrationnally assigned, adding about 1660 new assignments to those provided in the HITRAN database for 12 CH4 in the region. Graphical abstract: